Force plate use in performance monitoring and sport science testing - Beckham, G.; Suchomel, T.; Mizuguchi, S. (New Studies in Athletics, 2014)
Force plates are useful for examining the kinetic characteristics of an athlete's movement. They provide information about the external forces involved in movement that can aid a coach or sport scientist to quantitatively evaluate the athlete's execution of a skill or his/her physical development. Obtaining data of the highest quality and minimising error requires an understanding of the inner workings of a force plate, as well as the process by which data are transferred, processed and analysed. Knowledge of these helps validate whether the results produced are representative of what is actually happening on the force plate rather than error. The aim of this article is to inform coaches and other practitioners about the principles of force plate operation, including the theoretical basis, forces plate design and function, key aspects of data acquisition and technical information of note. The authors also provide a discussion of their laboratory's set up and their work with force plates as a practical example of how these tools can be used.